2022
DOI: 10.1371/journal.pone.0266827
|View full text |Cite
|
Sign up to set email alerts
|

Obesity modulates the immune macroenvironment associated with breast cancer development

Abstract: Growing evidence demonstrates a strong correlation between obesity and an increased risk of breast cancer, although the mechanisms involved have not been completely elucidated. Some reports have described a crosstalk between adipocytes, cancer cells, and immune cells within the tumor microenvironment, however, it is currently unknown whether obesity can promote tumor growth by inducing systemic alterations of the immune cell homeostasis in peripheral lymphoid organs and adipose tissue. Here, we used the E0771 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Many studies have shown that obesity induced proinflammatory cytokines promote metastasis in post-menopausal breast cancer [ 47 , 48 ]. Using diet-induced obesity murine models of E0771 breast cancer (aged above 14 weeks old at the time of tumor inoculation), it has been shown that HFD increases the levels of proinflammatory cytokines in the TME, which correlates with increased tumor size and lung metastasis [ 49 , 50 , 51 , 52 ]. However, in our E0771 implanted pubertal breast cancer model, a short-term HFD feeding in fact increased the latency of tumorigenesis compared to RD, which can be attributed to increased proinflammatory cytokines in the TEM in RD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that obesity induced proinflammatory cytokines promote metastasis in post-menopausal breast cancer [ 47 , 48 ]. Using diet-induced obesity murine models of E0771 breast cancer (aged above 14 weeks old at the time of tumor inoculation), it has been shown that HFD increases the levels of proinflammatory cytokines in the TME, which correlates with increased tumor size and lung metastasis [ 49 , 50 , 51 , 52 ]. However, in our E0771 implanted pubertal breast cancer model, a short-term HFD feeding in fact increased the latency of tumorigenesis compared to RD, which can be attributed to increased proinflammatory cytokines in the TEM in RD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-4 polarizes CD4 T cells towards the Th2 pro-tumor pattern ( Ostrand-Rosenberg, 2008 ). Experimental data indicate that the obesogenic environment significantly increases the percentage of intratumoral CD4 + cells and reduces CD8 counting in BC ( Elisia, 2020 ; Núñez-Ruiz A et al.,2022 ). Each increase of 10 units (kg/m2) in BMI in humans results in a 1.6% increase in CD4 + infiltration in the BC tissue ( Asad, Damicis, Heng, 2022 ), but no data about cytokines profile is available in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Using a DIO model implementing a HFD Lumeng et al 57 observed that obesity can significantly alter macrophage polarization within AT shifting from an M2 phenotype observed in lean control mice to an M1 https://doi.org/10.1038/s44324-024-00007-4 inflammatory phenotype indicated by increased expression of TNF and iNOS 57 . Although obesity has been associated with an increased M1 presence in AT, studies from DIO models have indicated that within the tumor microenvironment (TME), obesity can promote M2 skewing that adversely impacts immune responses and promotes tumor growth 58,59 . It is still not clear whether metabolic perturbations of obesity are responsible for this skewing, or the meta-inflammatory state associated with obesity.…”
Section: The Immune Landscape In Obesity and The Tumor Microenvironme...mentioning
confidence: 99%